Effect of Hydrophilic Polymers on Complexation Efficiency of Cyclodextrins in Enhancing Solubility and Release of Diflunisal - Bashir, Mehreen (Polymers (Basel), 2020)
The effects of three hydrophilic polymers, namely, carboxymethyl cellulose sodium (CMC-Na), polyvinyl alcohol (PVA) and poloxamer-188 (PXM-188) on the solubility and dissolution of diflunisal (DIF) in complexation with β-cyclodextrin (βCD) or hydroxypropyl β-cyclodextrin (HPβCD), were investigated. The kneading method was used at different drug to cyclodextrin weight ratios. Increases in solubility and drug release were observed with the DIF/βCD and DIF/HPβCD complexes. The addition of hydrophilic polymers at 2.5, 5.0 and 10.0% w/w markedly improved the complexation and solubilizing efficiency of βCD and HPβCD. Fourier-transform infrared (FTIR) showed that DIF was successfully included into the cyclodextrin cavity. Differential scanning calorimetry (DSC) and X-ray diffractometry (XRD) confirmed stronger drug amorphization and entrapment in the molecular cage of cyclodextrins. The addition of PVA, CMC-Na or PXM-188 reduced further the intensity of the DIF endothermic peak. Most of the sharp and intense peaks of DIF disappeared with the addition of hydrophilic polymers. In conclusion, PXM-188 at a weight ratio of 10.0% w/w was the best candidate in enhancing the solubility, stability and release of DIF.